2015
DOI: 10.1016/j.clnu.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Blood docosahexaenoic acid and eicosapentaenoic acid in vegans: Associations with age and gender and effects of an algal-derived omega-3 fatty acid supplement

Abstract: We conclude that vegans have low baseline omega-3 levels, but not lower than omnivores who also consume very little docosahexaenoic and eicosapentaenoic acids. The vegans responded robustly to a relatively low dose of a vegetarian omega-3 supplement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 27 publications
7
72
3
Order By: Relevance
“…In our study we did not find an association between circulating n-3 PUFAs and carotid IMT in a population of women of Hispanic origin. Although n-3 PUFA concentrations in our study population of Mexican women (mean v-3 index of 4.3%) are higher than what is observed in vegan populations (44)(45)(46) and similar to Hispanics living in the United States (9), we observed low n-3 PUFA concentrations relative to several populations (46)(47)(48). Thus, the lack of association observed in our study may be due to a limited distribution of the exposure.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…In our study we did not find an association between circulating n-3 PUFAs and carotid IMT in a population of women of Hispanic origin. Although n-3 PUFA concentrations in our study population of Mexican women (mean v-3 index of 4.3%) are higher than what is observed in vegan populations (44)(45)(46) and similar to Hispanics living in the United States (9), we observed low n-3 PUFA concentrations relative to several populations (46)(47)(48). Thus, the lack of association observed in our study may be due to a limited distribution of the exposure.…”
Section: Discussioncontrasting
confidence: 84%
“…Whole blood n-3 PUFAs were stored at room temperature, which may have caused uneven oxidation of the FAs and added preanalytic heterogeneity to our data. However, samples were collected in filter paper pretreated with antioxidants, and we have observed that values remain unchanged by oxidation for up to 2 wk at room temperature (44,45,54). CVs for EPA and DHA were moderate, and measurements were performed only on one occasion; thus, there is likely some measurement error.…”
Section: Discussionmentioning
confidence: 99%
“…Whole blood was chosen as the sample of choice because it is a global representation of circulating FA status (including both plasma and blood cells) and because analyses can be conducted on as little as a single drop. After collection, cards were stored in a re-sealable plastic bag at 4°C with batches delivered weekly to OmegaQuant Analytics for analysis by capillary gas chromatography as described previously [32]. Fatty acid levels are expressed both as a weight percent of total blood fatty acids (composition) and as a concentration (ug/mL blood).…”
Section: Methodsmentioning
confidence: 99%
“…Seven publications (describing six studies) met the inclusion criteria, which included two prospective cohort studies and five intervention studies ( Fig. 1) (29)(30)(31)(32)(33)(34)(35) . Two publications used the same data from one study and therefore the second publication (by date) was excluded (33) , resulting in a total of six publications being included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Sarter et al . and Geppert et al . used durations of 4 and 2 months, respectively, reporting both baseline and post‐supplementation omega‐3 indices, which provided a more rigorous depiction of algal supplementation in vegetarian populations.…”
Section: Discussionmentioning
confidence: 99%